2022
DOI: 10.17083/ijsg.v9i4.543
|View full text |Cite
|
Sign up to set email alerts
|

Examining Students’ Behavior in a Digital Simulation Game for Nurse Training

Abstract: Digital educational games have evolved in recent years due to the need to support education and training focused on non-technical skills. Data gathered through interaction with the graphical user interface are explored and exploited to analyze the players' experience. Many researchers have pointed the importance of analysis of players’ in-game behavior, which can help to enhance the learning process, identify learners' strategies, and improve the effectiveness of the serious game. This study is devoted to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Almost all articles used points as a calculation of student learning achievement. There were few articles that did not use point counting [33], [42], [75], [76], [44], [50], [52], [53], [57], [58], [64], [68]. In these articles, students only collected badges that can be obtained at each level completed.…”
Section: Addressing Review Question 1: the Elements Of Gamificationmentioning
confidence: 99%
“…Almost all articles used points as a calculation of student learning achievement. There were few articles that did not use point counting [33], [42], [75], [76], [44], [50], [52], [53], [57], [58], [64], [68]. In these articles, students only collected badges that can be obtained at each level completed.…”
Section: Addressing Review Question 1: the Elements Of Gamificationmentioning
confidence: 99%
“…Various types of games have been shown to be efficient for different educational purposes. For example, research by Novoseltseva et al (2022) revealed that the simulation features in digital games designed for specific academic subjects have proven beneficial in imparting content information and boosting learning. In addition, research by Hartt et al (2020) discovered that game elements that inspire delight, facilitate peer engagement, and allow the opportunity to share ideas have become increasingly beneficial in game design.…”
Section: Introductionmentioning
confidence: 99%
“…Computer games have become part of our daily lives in the past decades. It provides entertainment and sometimes educational tools like serious games [1]- [4]. One of the most popular computer games is the maze game.…”
Section: Introductionmentioning
confidence: 99%